Peningkatan Kompetensi Sumber Daya Manusia Relawan Eco School Nusantara Melalui Pendampingan Pembuatan Kerajinan Barang Bekas Dan Pembuatan Pupuk - Pujiarohman; Lalu Abdurrachman Wahid (AL HAYAT: Jurnal Pengabdian Masyarakat, 2023)
This service aims to improve the competency of human resources in the Indonesian eco school by providing assistance in making handicrafts from used goods and making fertilizer to provide knowledge about how to process unused waste into items of greater value and provide knowledge about how to make fertilizer from organic materials for gardening needs. Apart from increasing human resource competency, Eco School Archipelago volunteers also raise awareness of always caring about the surrounding environment so that it remains clean and safe from anything that could cause harm, both to humans and nature. The method used to increase the human resource competency of Indonesian Eco School volunteers is by providing direct training and practice, so that it can immediately stick to memory whatever has been learned during the process of making second-hand crafts and making fertilizer